2015
DOI: 10.1515/amm-2015-0405
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a Lamellar Structure – Effect of the True Interlamellar Spacing on the Durability of a Pearlite Colony / Stabilność Struktury Płytkowej – Wpływ Rzeczywistej Odległości Międzypłytkowej Na Trwałość Kolonii Perlitu

Abstract: StabIlIty of a lamellar Structure -effect of the true Interlamellar SpacIng on the durabIlIty of a pearlIte colony Stabilność Struktury płytkowej -wpływ rzeczywiStej odległości międzypłytkowej na trwałość kolonii perlituA lamellar microstructure is, beside a granular and dispersive one, the most frequently observed microstructure in the case of metal alloys. The most well-known lamellar microstructure is pearlite, a product of a eutectoidal transformation in the Fe-Fe3C system. The lamellar morphology of pearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…This is planned for future work, together with other tools, such as instrumental carbon analysis and conventional metallography based on etching using a set of experimentally produced samples.We stress that CSCE is designed for samples that have no directional preference in their microstructure, and where the grain size and BSE phase contrast are sufficiently large to enable an experienced operator to select suitable dark threshold and blur factor settings. Thus, we do not recommend using this tool for the carbon estimation of worked crucible steel samples with their often highly directional microstructures and small grain sizes, which negatively affect the distinction between broken primary cementite and cementite in spheroidized pearlite (Czarski et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This is planned for future work, together with other tools, such as instrumental carbon analysis and conventional metallography based on etching using a set of experimentally produced samples.We stress that CSCE is designed for samples that have no directional preference in their microstructure, and where the grain size and BSE phase contrast are sufficiently large to enable an experienced operator to select suitable dark threshold and blur factor settings. Thus, we do not recommend using this tool for the carbon estimation of worked crucible steel samples with their often highly directional microstructures and small grain sizes, which negatively affect the distinction between broken primary cementite and cementite in spheroidized pearlite (Czarski et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In bearing steel, there is an intimate relationship between the morphology of pearlite and the subsequent spheroidising structure. Czarski et al [8] found that the stability (durability) of cementite in pearlite was enhanced with the increase of interlamellar spacing. Therefore, the time required for spheroidising annealing was equivalent longer.…”
Section: Introductionmentioning
confidence: 99%
“…One possible way to refine final martensitic structure is refinement of the soft annealed structure before quenching. A conventional soft annealing schedule consists of long-term soaking at a temperature near A c1 and subsequent cooling in the furnace [3,4]. Spheroidisation process can be accelerated by rapid austenitization followed by divorced pearlitic transformation.…”
Section: Introductionmentioning
confidence: 99%